Molecular Dynamics Simulations of Platinum Plasma Sputtering: A Comparative Case Study - Brault, Pascal; Chuon, Sotheara; Bauchire, Jean-Marc (Frontiers in Physics, 2016)
Molecular Dynamics simulations are carried out for investigating atomic processes of platinum sputtering. Sputtered Pt atom energy distribution functions (EDF) are determined at different sputtering argon ionenergies: 100, 500, and 1000 eV. Calculated EDF show a cross-over from Thompson theory to binary collision model when increasing argon ion energy and Pt atom sputtered energy. Implanted argon ion number is depending on its kinetic energy, while it is not the case in binary collision approximation. Finally sputtering yields are greater for Thompson theory than for binary collision model at low energy, but converge to the close values at high energy.